EFFECT OF MINERAL NUTRIENTS AND GROWTH REGULATORS ON MANAGEMENT OF FRUIT DROP AND IMPROVEMENT OF ON MANAGEMENT OF FRUIT DROP AND IMPROVEMENT OF FRUIT QUALITY IN KINNOW MANDARIN - KAUR, RAMANDEEP; KAUR, NIRMALJIT (The Bioscan, 2016)
The present investigation on the effect of the foliar application of micronutrients and growth regulators on management of fruit drop concomitant with improvement of fruit quality in Kinnow mandarin was carried out at Punjab Agricultural University, Ludhiana during 2012-2013. Minimum fruit drop percent and maximum fruit retention per cent were recorded with the foliar application of MgSO4 (0.6%). A significant increase in yield due to reduction in per cent fruit drop when compared to control has been recorded with the application of KNO3+2,4-D (2.5+20µg/ml). The maximum fruit weight (232g/fruit), size (6.51x7.44cm), TSS:Acid ratio (15.0), Vitamin C (50.46 mg/100 ml juice), juice per cent (54.66%), flavonoids (24.96 mg/g equivalent); and a minimum rag per cent (20.26%) were recorded with the application of KNO3+2,4-D (2.5+20µg/ml). Thus the synergistic effect of KNO3 +2,4-D (2.5% and 20µg/ml) improves fruit yield and quality in Kinnow mandarin by reducing the fruit drop.